ARGUMENTATIVE STRATEGIES AND LOCUTOR ATTITUDE IN JUDGMENTS OF SUPREME COURTS OF FRANCE AND SPAIN - CUNILLERA, Montserrat; REY, Joëlle (Comparative Legilinguistics, 2017)
Legal texts are closely linked to the linguistic and cultural community in which they are produced and as such they reflect the power relations existing between its members. They are highly complex texts submitted to rigid linguistic conventions. However, as Anscombre and Ducrot (1983) pointed out, any linguistic unit contains semantic and pragmatic instructions which trigger a certain argumentative orientation and reflect the point of view of the speaker (Raccah 2005). This analysis, which is based on a corpus of sentences dictated by the French Cour de Cassation and the Spanish Sala Primera de lo Civil del Tribunal Supremo, analyses, on the one hand, the expressions used to refer to the speaker or the institution involved and, on the other hand, the discourse markers used to articulate textual sequences. The contrastive analysis provides evidence that, under an apparent objectivity, these texts convey numerous points of view which are characteristics of this type of texts both on macrotextual and microtextual levels.